Sociology and climate change - Miltojević, Vesna D.; Ilić Krstić, Ivana (Sociološki pregled, 2021)
This paper showcases the necessity of a multidisciplinary approach to the examination of causes and effects of climate change, particularly the necessity of greater involvement of sociologists in the investigation of the causes and the offering of solutions to mitigate the effects. Accepting the view that present-day climate change is socially conditioned, the discussion relies on the assumption that climate change has indeed found its place in sociological research, only not to a sufficient extent. Based on the review of available literature, it was determined that the study of climate change was triggered by social ecologists and that climate change became a full-fledged subject of theoretical considerations and investigations into specific causes and effects. Since agriculture is one of the causes of climate change, the paper emphasizes the necessity of sociological research of the agricultural sector and its relation to climate change and proposes other potential research fields.